The nexus between creative workforce and economic development: looking for the causal relation - Antonio Paolo Russo; Alan Quaglieri Domínguez; Alessandro Crociata; Massimiliano Agovino (European Regional Science Association (ERSA), 2012)
Building on work funded by the ESPON 2013 Program, the paper analyses the regional trajectories of development of a "creative workforce" among its active population against regional economic growth, measured by changes in per capita GDP over the period 2001-2008 in 317 NUTS2 regions of the ESPON space (EU29 plus partner and candidate countries). The analysis establishes and explores regional typologies in this relationship, but also addresses the issue of causal relationships between the two dimensions, trying to bridge different perspectives: an "industrial district" approach by which creative places are more innovative and thus have higher chances to grow, and a "new geographic" approach à la Florida by which wealthier (and not only in economic terms, so we bring in other dimensions to this study related with quality of place) places have higher chances to attract the creatives, whether or not this really translate into economic development. This is issue is of particular relevance for policymakers designing regional development strategies around innovation issues: is it more important to focus on attracting creatives through "place investments" so that potentials for innovation are boosted, or to make sure that localised creativity is transformed into real opportunities for growth? And, how is the regional context influencing that decision? We will employ statistical techniques on available data series for this analysis, but we will also look at concrete cases of different typologies of regions where this relation seems to have been working in opposite directions, trying to identify the determinants.
Keywords: Z10; O15; R11; 330; Creative workforce; innovation; economic development; causality